2004
DOI: 10.1007/bf02830582
|View full text |Cite
|
Sign up to set email alerts
|

Influence of moisture on the crystal forms of niclosamide obtained from acetone and ethyl acetate

Abstract: ABSTRACTof solvated or hydrated crystal forms, crystals in which the solvent molecules occupy regular positions in the crystal lattice, is widespread among compounds of pharmaceutical interest. 4,5 The behavior of pharmaceutical hydrates in response to changes in environmental conditions can have a significant impact on the development process and dosageform performance. The obvious situation that favors the formation of hydrates is recrystallization, using water as a solvent. However, recrystallization using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The relationship between the two niclosamide monohydrates was studied further by a range of methods, which consistently suggest that H A is the kinetically favoured form which readily transforms into H B . (Manek & Kolling, 2004, Tian et al, 2010, van Tonder, Mahlatji, et al, 2004 Physical property measurements reported on the solvates listed above, including solubility, dissolution and thermal properties, revealed a high affinity for water of all these crystal forms. (van Tonder, Mahlatji, et al, 2004, van Tonder, Maleka, et al, 2004 This may have potentially impacted some of the measurements reported, given that, for example, niclosamide tetrahydrofuran solvate crystals are reported to undergo desolvation within minutes of being removed from the mother liquor.…”
Section: Figurementioning
confidence: 98%
See 1 more Smart Citation
“…The relationship between the two niclosamide monohydrates was studied further by a range of methods, which consistently suggest that H A is the kinetically favoured form which readily transforms into H B . (Manek & Kolling, 2004, Tian et al, 2010, van Tonder, Mahlatji, et al, 2004 Physical property measurements reported on the solvates listed above, including solubility, dissolution and thermal properties, revealed a high affinity for water of all these crystal forms. (van Tonder, Mahlatji, et al, 2004, van Tonder, Maleka, et al, 2004 This may have potentially impacted some of the measurements reported, given that, for example, niclosamide tetrahydrofuran solvate crystals are reported to undergo desolvation within minutes of being removed from the mother liquor.…”
Section: Figurementioning
confidence: 98%
“…The structure of monohydrate H A has remained unknown, although its significantly lower dehydration temperature (373 K) suggests that the water-molecule inclusion mode is substantially different from that in H B . The relationship between the two NCL monohydrates has been studied further by a range of methods, which consistently suggest that H A is the kinetically favoured form which readily transforms into H B (Manek & Kolling, 2004;Tian et al, 2010;van Tonder, Mahlatji et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…4 The crystalline form in which most drugs exist affects their solidstate characteristics. 5,6 Generally, the way drugs react plays a signicant role on their performance characteristics. NC has been reported to crystallize into two solvate forms: two monohydrates (H A and H B ) and one anhydrous.…”
Section: Introductionmentioning
confidence: 99%
“…If a crystallization process generates a metastable intermediary form, it can absorb water when exposed to moisture and change into a hydrate. Water molecules, because of their small size and multidirectional hydrogen bonding capabilities, are particularly suited to fill structural voids (Manek & Kolling, 2004). If a crystallization system is open to atmospheric conditions, as is likely to be the case with evaporative crystallization, hygroscopic solvents will absorb moisture from the air if present.…”
Section: Moisture and Humiditymentioning
confidence: 99%